Global maternal health and newborn health: Looking backwards to learn from history. (October 2016) - Bergström, Staffan
Abstract : The late appearance of the 'M' on the international health agenda – in its own right and not just as a carrier of the intrauterine passenger – is thought-provoking. The 'M' was absent for decades in textbooks of 'tropical medicine' until the rhetoric question was formulated: 'Where is the "M" in MCH?' The selective antenatal 'high-risk approach' gained momentum but had to give way to the fact that all pregnant women are at risk due to unforeseeable complications. In order to provide trained staff to master such complications in impoverished rural areas (with no doctors), some countries have embarked on training of non-physician clinicians/associate clinicians for major surgery with excellent results in 'task-shifting' practice. The alleged but non-existent 'human right' to survive birth demonstrates that there have been no concrete accountability and no 'legal teeth' to make a failing accountability legally actionable to guarantee such a right. Highlights: Maternal ill health had been a neglected entity until the 1980s. Maternal and neonatal survival deserves priority after the failure of MDG 5. When the woman dies a maternal death, the baby is almost never on her back.